Sodium secondary battery and high-voltage ether electrolyte thereof

By combining ether solvent compositions with NaPF6, the problems of oxidation stability and low electrochemical window of ether electrolytes were solved, achieving high electrochemical performance and optimized voltage window, thus improving the overall performance of sodium-ion batteries.

CN120854673APending Publication Date: 2025-10-28CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511018264.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing ether electrolytes have poor oxidative stability and low electrochemical window, making them difficult to match with high-voltage positive electrodes, limiting their application in high-energy-density sodium-ion batteries. Existing additive improvement solutions are also difficult to achieve both good window and electrochemical performance.

Method used

A high-concentration ether solvent composition, including small-ring type 1, macro-ring type 2 and linear diether type 3, combined with an appropriate amount of NaPF6, is used to achieve a synergistic effect through the joint control of ratio and concentration, thereby achieving high electrochemical performance and optimized voltage window without the need for additional additives.

Benefits of technology

A high electrochemical window voltage was achieved without the need for additional additives, while maintaining excellent rate, low temperature, high temperature and high current cycling stability, thus improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120854673A_ABST
    Figure CN120854673A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrolytes, and particularly relates to a sodium secondary battery and a high-voltage ether electrolyte thereof, the high-voltage ether electrolyte comprises an ether solvent and NaPF6; the ether solvent comprises a formula 1 (1), a formula 2 (2) and a formula 3 (3); r1 is alkyl of C1-C3, and X is CH or O; r2 is alkyl with 1 to 3 carbon atoms; wherein in the ether solvent, the volume ratio of the formula 1 to the formula 2 is (1-4): 1, and the volume content of the formula 3 is 80-95%. According to the invention, the formula 1, the formula 2 and the formula 3 are innovatively combined, and are further adaptively combined with NaPF6 based on the combined control of the proportion of the three, so that synergy can be accidentally realized, excellent window voltage can be obtained on the premise of no need of additional additives, and in addition, excellent electrochemical performance can be taken into account, for example, the preparation method is simple and convenient. The electrolyte provided by the invention also has excellent multiplying power, low temperature, high temperature and large current cycling stability on the premise of considering high window voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and more specifically to the field of electrolytes. Background Technology

[0002] Driven by the large-scale application of renewable energy and the continuous advancement of electric vehicle technology, secondary battery energy storage systems are experiencing significant growth. Sodium-ion batteries (SIBs), as a technology with outstanding cost-effectiveness, are attracting increasing attention. Hard carbon (HC) batteries, due to their theoretical specific capacity >500 mAh g⁻¹, are also gaining popularity. -1 With advantages such as low operating potential, it is expected to become the first industrialized sodium-based anode material, promoting the commercial application of SIBs. However, low initial coulombic efficiency (ICE), poor rate performance, and limited cycle stability have always been obstacles to the application of HC. Compared with the high cost and long industrialization cycle of technologies such as material microstructure control, electrolyte engineering optimization based on existing HC materials is the most effective strategy to improve the electrochemical performance of HC. Due to the different solvent properties, the compatibility between ester-based electrolytes and HC is not as good as that between ether-based electrolytes, which leads to the better physicochemical performance of HC anodes in ether-based electrolytes than in ester-based electrolytes. For example, patent document CN120221784A discloses an electrolyte formulation in the field of sodium secondary battery technology, which mixes diethylene glycol dimethyl ether and sodium tetrafluoroborate in a certain molar ratio to form a new slightly soluble electrolyte. Unfortunately, traditional ether-based electrolytes often have poor oxidation stability and a low electrochemical window (ESW) (< 4.0 V vs. Na). + Sodium ion batteries (Na₂O) are difficult to adapt to high-voltage cathodes (such as layered oxide cathodes), which severely limits their application in high-energy-density sodium-ion batteries.

[0003] To address the issue of low electrolyte window in ether-based electrolytes, existing technologies have proposed numerous improvement strategies using additives. For example, patent document CN120109292A discloses an electrolyte comprising a sodium salt, an organic solvent, and additives; the organic solvent is an ether solvent; the additives are selected from non-sodium metal salts; the non-sodium metal salts are selected from at least one of a first additive, a second additive, or a third additive; wherein the first additive is a lithium metal salt; the second additive is a magnesium metal salt; and the third additive is an aluminum metal salt. While these additive-based window-improving schemes can enhance the window to some extent, they introduce heterogeneous impurities, and the degree of window improvement still needs further refinement. Furthermore, existing solutions struggle to balance a good window and good electrochemical performance.

[0004] Therefore, there is an urgent need to develop an ether-based electrolyte that combines high oxidation stability and high ionic conductivity with excellent window and electrochemical performance. Summary of the Invention

[0005] To address the problem that existing ether electrolytes struggle to achieve both a high electrolyte window and high electrochemical performance, the primary objective of this invention is to provide a high-voltage ether electrolyte that maintains excellent high electrolyte window and electrochemical performance without the addition of external additives.

[0006] A second objective of this invention is to provide a sodium-ion battery comprising the aforementioned high-voltage ether electrolyte.

[0007] To improve the electrochemical window of ether electrolytes, high-concentration electrolytes, locally high-concentration electrolytes, and weakly solvated electrolytes with different configurations have been proposed. However, high-concentration or locally high-concentration electrolytes are expensive, have high viscosity, and low ionic conductivity, severely limiting battery rate performance and commercial application. Weakly solvated electrolytes also have very limited ionic conductivity due to insufficient salt dissociation. Furthermore, single weakly coordinating solvents often have poor oxidation resistance, making it difficult to achieve ideal optimization of the electrolyte window. To address this technical problem, this invention, after in-depth research, provides the following improvement:

[0008] A high-voltage ether electrolyte comprising an ether solvent and NaPF6;

[0009] The ether solvents include those of Formula 1, Formula 2 and Formula 3;

[0010] Formula 1

[0011] Formula 2

[0012] Formula 3

[0013] R1 is a C1~C3 alkyl group, and X is CH or O; R2 is a C1~C3 alkyl group;

[0014] The volume ratio of Formula 1 to Formula 2 is 1 to 4:1; in the ether solvent, the volume content of Formula 3 is 80 to 95%.

[0015] This invention innovatively combines small-ring type 1 and large-ring type 2 with R-branched structures and linear diether type 3, and further coordinates the ratio of the three and the joint control of NaPF6. This unexpectedly achieves synergy, enabling the attainment of excellent window voltage without the need for additional additives. In addition, it also achieves excellent electrochemical performance. For example, the electrolyte described in this invention, while maintaining a high window voltage, also exhibits excellent rate capability, low-temperature, high-temperature, and high-current cycling stability.

[0016] In this invention, Formula 1 is Formula 1A; Formula 2 is Formula 2A; and Formula 3 is Formula 3A.

[0017] Formula 1A;

[0018] Formula 2A;

[0019] Formula 3A.

[0020] In this invention, the combined control of the ratio of Formula 1 and Formula 2 and the percentages between the components is key to adapting and synergizing with NaPF6, thereby enabling it to exhibit excellent window voltage and excellent electrochemical performance without additional additives.

[0021] Preferably, the volume ratio of Formula 1 to Formula 2 is 1.3 to 1.6:1; and the volume content of Formula 3 in the ether solvent is 88 to 92%. Studies have shown that the preferred solvent system can further optimize the electrochemical behavior and help to further enhance the rate capability, high voltage, and low temperature performance of the electrolyte.

[0022] Preferably, the concentration of NaPF6 is 0.1~2.0 M.

[0023] Preferably, the concentration of NaPF6 is 0.45~0.65 M; more preferably 0.49~0.51 M; and even more preferably 0.5 M. This invention demonstrates that, in the combined system of the ether solvent and NaPF6, further control of the ratio and concentration can enhance the synergistic effect, contributing to further improvements in the rate capability, high voltage, and low-temperature performance of the electrolyte.

[0024] The electrolyte described in this invention, through the combination of ether solvents and the composition and ratio of NaPF6, can synergistically achieve excellent rate capability, low temperature, high temperature and high current cycling stability at a relatively low NaPF6 concentration.

[0025] The present invention also provides a sodium secondary battery comprising the aforementioned high-voltage ether electrolyte.

[0026] In this invention, the sodium secondary battery, apart from containing the high-voltage ether electrolyte described in this invention, may have other known components and structures.

[0027] The sodium secondary battery of the present invention is a sodium-ion battery or a sodium battery without a negative electrode.

[0028] The sodium secondary battery high-voltage sodium secondary battery of the present invention has a positive electrode active material in its positive electrode that is a high-voltage positive electrode active material.

[0029] The high-voltage positive electrode active material of the present invention includes at least one of sodium manganate, sodium ferromanganate, sodium nickel ferromanganate, sodium nickel manganate, sodium chromate, sodium vanadium phosphate, sodium iron phosphate, sodium iron pyrophosphate, sodium iron sulfate, and sodium vanadium fluorophosphate.

[0030] The active material in the negative electrode of the sodium secondary battery of the present invention is sodium metal, sodium alloy, carbon negative electrode active material, silicon negative electrode active material or carbon-silicon composite active material.

[0031] Beneficial effects

[0032] This invention innovatively combines Formulas 1, 2, and 3, and further adapts and combines them with NaPF6 based on the joint control of their proportions. This unexpectedly achieves synergy, enabling the attainment of excellent window voltage without the need for additional additives. In addition, it also takes into account excellent electrochemical performance. For example, the electrolyte described in this invention, while taking into account high window voltage, also has excellent rate capability, low temperature, high temperature, and high current cycling stability. Attached Figure Description

[0033] Figure 1 The constant current charge-discharge curve of the HC half-cell when tested with the electrolyte obtained in Example 1 at room temperature;

[0034] Figure 2 The rate performance of the HC half-cell when tested with the electrolyte obtained in Example 1 at room temperature;

[0035] Figure 3 The cycle performance of the HC half-cell when tested with the electrolyte obtained in Example 1 at room temperature;

[0036] Figure 4 The LSV curve of the Na / stainless steel battery tested at room temperature using the electrolyte obtained in Example 1;

[0037] Figure 5 The rate performance of the HC / sodium nickel manganese oxide full cell tested at room temperature using the electrolyte obtained in Example 1;

[0038] Figure 6 The cycle performance of the HC half-cell was tested at a low temperature of -20°C using the electrolyte obtained in Example 1. Detailed Implementation

[0039] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0040] Example 1

[0041] A low-concentration, high-pressure ether-based electrolyte and its application are disclosed. The composition of the electrolyte is shown in the table below.

[0042]

[0043] The electrolyte provided in Example 1 was applied to a sodium-ion battery.

[0044] Sodium-ion button half-cell rate and cycle test: The positive electrode side is a hard carbon positive electrode (containing a positive current collector (Al foil) and a positive electrode material composited on its surface, the positive electrode material containing hard carbon, PVDF and acetylene black in a weight ratio of 8:1:1), the counter electrode is metallic sodium, and the test voltage range is 0.01-3 V.

[0045] Sodium-ion coin cell rate test: The positive electrode side is sodium nickel iron manganese oxide (NaMn). 1 / 3 Fe 1 / 3 Ni 1 / 3 O2) Positive electrode (comprising a positive current collector (Al foil) and a positive electrode material composited on its surface, the positive electrode material containing NaMn in a weight ratio of 8:1:1) 1 / 3 Fe 1 / 3 Ni 1 / 3 O2, PVDF and Super P, with a hard carbon negative electrode on the negative side (containing a negative current collector (Al foil) and a negative electrode material composited on its surface, the negative electrode material containing hard carbon, PVDF and acetylene black in a weight ratio of 8:1:1), and a test voltage range of 1.0-4.0 V.

[0046] Button-type half-cells or full cells were assembled in a glove box filled with high-purity argon (O2 < 0.1 ppm, H2O < 0.1 ppm). The battery testing environment was room temperature (25℃) or -20℃, and the half-cell rate testing current density was 0.03-0.05-0.1-0.2-0.4-0.8-1.0-2.0-0.03 Ag. -1 (Results are shown in Table 1).

[0047] Electrolyte LSV window testing was conducted using a Na / stainless steel battery, with a cutoff voltage of 6.0V. The scan rate was 1 mV / s. -1 (Results are shown in Table 2).

[0048] The results are as follows: Figure 1 As shown, during the first discharge, the hard carbon material provided 485.1 mAh g⁻¹ in the constructed electrolyte. -1 It exhibits a high discharge capacity, with an ICE of 72.1%. Simultaneously, hard carbon materials demonstrate excellent rate performance in the constructed electrolyte. Figure 2 and outstanding and stable cycle performance. Figure 3 Voltage window () Figure 4 Tests show that the constructed novel ether-based electrolyte has an ultra-high electrochemical window of 5.12V.

[0049] To verify the practical applicability of the obtained electrolyte, a coin cell was assembled using high-voltage sodium nickel iron manganese oxide as the positive electrode and hard carbon as the negative electrode. Figure 5As shown, the full cell exhibits excellent rate performance under conditions of 0.1C to 1C. To further demonstrate the low-temperature performance of the obtained electrolyte, cycle performance tests of hard carbon coin half-cells were conducted at -20°C, as shown below. Figure 6 As shown, the battery still has ideal output capacity and cycle stability under low temperature conditions, indicating that under low concentration conditions, the combination of Formulas 1 to 3 can construct an ether-based electrolyte with both high oxidation stability and high ionic conductivity.

[0050] Example 2

[0051] Compared with Example 1, the only difference is that the volume ratio of Formula 1A and Formula 2A is changed, while the percentage of their total amount in the ether solvent is the same as in Example 1. The experimental groups are as follows:

[0052] Group A: The volume ratio of Equation 1A and Equation 2A is 1:1;

[0053] Group B: The volume ratio of Equation 1A to Equation 2A is 4:1.

[0054] All other operations and parameters are the same as in Example 1.

[0055] Example 3

[0056] Compared with Example 1, the only difference is that the percentage of Formula 3A in the ether solvent is changed. The proportions of Formula 1A and Formula 2A, as well as other operations and parameters, are the same as in Example 1. The experimental groups are as follows:

[0057] Group A: Formula 3A has a volume ratio of 80% in ether solvents;

[0058] Group B: Formula 3A has a volume ratio of 95% in ether solvents.

[0059] All other operations and parameters are the same as in Example 1.

[0060] Example 4

[0061] Compared to Example 1, the only difference was the change in the concentration of NaPF6. The experimental groups were as follows:

[0062] Group A: The concentration of NaPF6 is 0.45 M;

[0063] Group B: The concentration of NaPF6 is 0.6 M;

[0064] All other operations and parameters are the same as in Example 1.

[0065] Comparative Example 1

[0066] Compared with Example 1, the only difference is that the ether solvent is only Formula 1A, and the NaPF6 concentration and other operations and parameters are the same as in Example 1.

[0067] Comparative Example 2

[0068] Compared with Example 1, the only difference is that the ether solvent is only Formula 2A, and the NaPF6 concentration and other operations and parameters are the same as in Example 1.

[0069] Comparative Example 3

[0070] Compared with Example 1, the only difference is that the ether solvent is only Formula 3A, and the NaPF6 concentration and other operations and parameters are the same as in Example 1.

[0071] Comparative Example 4

[0072] Compared with Example 1, the only difference is that Formula 1A is missing in the ether solvent, and the missing Formula 1A is made up by an equal volume of Formula 2A. The NaPF6 concentration and other operations and parameters are the same as in Example 1.

[0073] Comparative Example 5

[0074] Compared with Example 1, the only difference is that Formula 2A is missing in the ether solvent, and the missing Formula 2A is made up by an equal volume of Formula 1A. The NaPF6 concentration and other operations and parameters are the same as in Example 1.

[0075] Comparative Example 6

[0076] Compared with Example 1, the only difference is that Formula 3A is missing in the ether solvent, and the missing Formula 3A is supplemented by Formula 1A and Formula 2A. The ratio of Formula 1A and Formula 2A and the NaPF6 concentration are the same as in Example 1.

[0077] Comparative Example 7

[0078] Compared with Example 1, the only difference is that the volume ratio of Formula 1A to Formula 2A in the ether solvent is 1:2.3, and the content of Formula 3A, the concentration of NaPF6, and other operations and parameters in the ether solvent are the same as in Example 1.

[0079] Comparative Example 8

[0080] Compared with Example 1, the only difference is that the volume ratio of Formula 1A to Formula 2A in the ether solvent is 9:1, and the content, concentration, and other operations and parameters of Formula 3A in the ether solvent are the same as in Example 1.

[0081] Comparative Example 9

[0082] Compared with Example 1, the only difference is that the content of Formula 3A in the ether solvent is 30%, while the ratio of Formula 1A and Formula 2A, as well as other operations and parameters of NaPF6, are the same as in Example 1.

[0083] Comparative Example 10

[0084] Compared with Example 1, the only difference is that NaPF6 is replaced with an equimolar amount of NaTFSI; all other operations and parameters are the same as in Example 1.

[0085] The results for each case are shown in Tables 1 through 4:

[0086]

[0087]

[0088]

[0089]

[0090] As shown in Tables 1 to 4, this invention innovatively combines Formulas 1, 2, and 3, and further adapts and combines them with NaPF6 based on the joint control of their proportions. This unexpectedly achieves synergy, enabling the attainment of excellent window voltage without the need for additional additives. In addition, it also takes into account excellent electrochemical performance. For example, the electrolyte described in this invention, while taking into account high window voltage, also has excellent rate capability, low temperature, high temperature, and high current cycling stability.

Claims

1. A high-voltage ether electrolyte, characterized in that, Contains ether solvents and NaPF6; The ether solvents include those of Formula 1, Formula 2 and Formula 3; Formula 1 Formula 2 Formula 3 R1 is a C1~C3 alkyl group, and X is CH or O; R2 is a C1~C3 alkyl group; In the ether solvent, the volume ratio of Formula 1 and Formula 2 is 1 to 4:1, and the volume content of Formula 3 is 80 to 95%.

2. The high-voltage ether electrolyte as described in claim 1, characterized in that, Equation 1 is Equation 1A; Equation 2 is Equation 2A; Equation 3 is Equation 3A; Formula 1A; Formula 2A; Formula 3A.

3. The high-voltage ether electrolyte as described in claim 1, characterized in that, The volume ratio of Formula 1 to Formula 2 is 1.3 to 1.6:1; in ether solvents, the volume content of Formula 3 is 88 to 92%.

4. The high-voltage ether electrolyte according to any one of claims 1 to 3, characterized in that, The concentration of NaPF6 is 0.1~2.0 M.

5. The high-voltage ether electrolyte as described in claim 4, characterized in that, The concentration of NaPF6 is 0.45~0.65M.

6. A sodium secondary battery, characterized in that, It includes the high-voltage ether electrolyte as described in any one of claims 1 to 5.

7. The sodium secondary battery as described in claim 6, characterized in that, The sodium secondary battery mentioned is a sodium-ion battery or a sodium battery without a negative electrode.

8. The sodium secondary battery as described in claim 6, characterized in that, The sodium secondary battery described above is a high-voltage sodium secondary battery, in which the positive electrode active material is a high-voltage positive electrode active material.

9. The sodium secondary battery as described in claim 8, characterized in that, The high-voltage positive electrode active material includes at least one of sodium manganate, sodium ferromanganate, sodium nickel ferromanganate, sodium nickel manganate, sodium chromate, sodium vanadium phosphate, sodium iron phosphate, sodium iron pyrophosphate, sodium iron sulfate, and sodium vanadium fluorophosphate.

10. The sodium secondary battery according to any one of claims 6 to 9, characterized in that, The active material in the negative electrode of a sodium secondary battery is sodium metal, sodium alloy, carbon negative electrode active material, silicon negative electrode active material, or carbon-silicon composite active material.

Citation Information

Patent Citations

  • Electrolyte and sodium ion battery containing same

    CN120109292A

  • Slightly soluble electrolyte, sodium secondary battery and electric equipment

    CN120221784A